RELASI MITOS, DAN AGAMA SEBAGAI MEDIA PENINGKATAN EKONOMI PRODUKTIF DALAM TRADISI “TEBOKAN” DI DESA KALIPUTU KOTA KUDUS - Saifuddin Saifuddin (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2013)
“Tebokan” was the history of jenang production processes that was visualizedon cultural carnival. It was one of the place where the relationship of religious traditions and the myth of local society became a new spirit to increase the economy of the community. This research was based on interpretative perspective to religious behaviors such as done by Clifford Geertz. Therefore this research used qualitative method. This study found the cultural illustrations where the relationship of myth, religious tradition, and the social structure was able to activate spirit of productivity in the Kaliputu Society as a central of jenang Production in Kudus. Both of these systems of meaning were able to present three important spirits, those areinnovative, identity affirmation, and work ethic.